Vocal Participation and Democratic Resilience: Navigating into Speech Visibility and Institutional Responsiveness - Agyare, Patrick (Technium Social Sciences Journal, 2025)
This paper examines how vocal participation, communicative visibility, and dissent shape democratic resilience across institutional, legal, educational, and civic contexts. Moving beyond normative theory, democracy is conceptualized as a communicative system in which voice and silence structure institutional behavior and epistemic legitimacy. Drawing on critical-institutionalist and deliberative frameworks, three propositions—Democratic Efficacy, Deliberative Robustness, and the Spiral Counter—are tested through six case studies: Norway’s NAV social security misinterpretation; Norway’s Barnevernet case–parents’ appeals to the European Court of Human Rights; U.S. federal court deportation reversals; democratic pressures in India; minority visibility in Australian educational materials; and Canadian police-reported hate crime statistics. These events illustrate how visibility, voice, and institutional response interact. Using comparative indices of Speech–Responsiveness, Deliberative Robustness, and Resistance Spirals, this paper demonstrates that dissent and openness generate corrective feedback, while suppression fosters distortion and drift. Legitimacy in democratic systems emerges not solely through deliberation but also through contestation, as the presence of disagreement enables epistemic correction. Conversely, silence—whether imposed or internalized—constrains mechanisms of correction and narrows democratic possibility, reducing the inclusivity and adaptability of democratic legitimacy.